Regional odontodysplasia: a case report - Ruezga-García, Claudia Alejandra (2019)
The regional odontodysplasia (RO) is a rare development anomaly that involves components of the ectoderm and mesoderm, this alteration affects both temporary and permanent dentition, being the maxilla more frequently affected than the mandible. A 13-year-old male patient presented delayed eruption of dental organs 21 to 24. Intraoral examination of the soft tissues had normal characteristics, an incomplete formation of the dental organs was distinguished without achieving a distinction in the opacity between enamel and dentin, with wide pulp chambers. We proceeded to the surgical extraction of teeth 21 to 24, a month after this, temporary prosthetic rehabilitation was performed. The RO is a little described alteration so it is still necessary to clarify the etiology and long-term evolution of the condition, the disclosure of new cases will allow to expand the knowledge regarding its frequency, as well as to raise awareness among the health professional about the presence and treatment of it.